Top-down and bottom-up processing in listening comprehension (Journal of Universal Science Research, 2023)
The top-down and bottom-up processing of a piece of information in academic listening are the topics of this article. In order to help language learners become proficient communicators in a communicative competence framework, it is equally crucial to activate prior knowledge and expectations through lexical access (top-down) and to piece together linguistic data until a contextual meaning of an utterance is reached (bottom-up). As a result, the two processes are combined in modern teaching tactics or techniques used to increase listening skills. For some teaching goals, especially in English for Specific Purposes (ESP) course, it may appear more practical to take a top-down approach to academic listening while ignoring a bottom-up one. Top-down processing directs the listening process and creates a connection with higher level reasoning in the course at TSUUL that is specifically developed for third-year students.